Egg yolk immunoglobulin Y administration on Salmonella Typhimurium colonization, intestinal health, and growth performance in broiler chickens - Mona Moosavi; Shaban Rahimi; Mohammad Amir Karimi Torshizi; Taghi Zahraei Salehi; Jesse Grimes (Poultry Science)
Salmonella Typhimurium (ST) is a major foodborne pathogen primarily transmitted through poultry products. Effective alternative strategies are essential because of restrictions on antibiotic usage as a primary treatment to control this pathogen. Thus, this study aimed to compare the effect of IgY's different administration methods on reducing Salmonella Typhimurium colonization in broiler chickens' intestines, intestinal health, and integrity, as well as its impact on growth performance and immune responses. Three hundred and twenty-day-old Ross 308 broiler chicks were divided into eight groups and monitored for 42 d. Seven groups were orally inoculated with 1 mL ST suspension (1.5 × 10⁸ CFU/mL) on days 7 and 8 and received treatments, including specific and non-specific powder (5 g/kg), and IgY administrated via drinking water (8.3 mL/L), encapsulated IgY (CIPY) (11.5 g/kg), and antibiotic (1 mL/L, days 8-13), alongside positive and negative controls. Based on these results CIPY and antibiotic groups considerably decreased Salmonella colonization in the liver and ceca (P < 0.05). Encapsulated IgY also improved intestinal health and integrity by increasing villus height (VH) (P < 0.05) and villus height-to-crypt depth ratio (VH: CD) (P < 0.05). Inflammatory serum markers, including INF-γ and IL-10, in response to the CIPY and antibiotic groups significantly decreased compared to the other groups (P < 0.05). Additionally, the weight of the bursa of Fabricius was significantly enhanced in the encapsulated IgY group and serum IgY concentration was also highest throughout the experiment period in the CIPY group (P < 0.05), indicating the improvement of the immune response in this group compared to the non-encapsulated specific IgY group. No significant differences in weight gain were observed across treatments (P > 0.05); however, the feed conversion ratio (FCR) was significantly improved in the encapsulated IgY group (P < 0.05). Based on these results, encapsulated IgY (CIPY) can be a promising antibiotic alternative effectively reducing Salmonella colonization and improving intestinal health and immune responses in broiler chickens.